Urolithin a attenuates IL-1β-induced inflammatory responses and cartilage degradation via inhibiting the MAPK/NF-κB signaling pathways in rat articular chondrocytes - Sheng-long Ding; Zhi-ying Pang; Xue-mei Chen; Zheng Li; Xin-xin Liu; Qi-lin Zhai; Jun-ming Huang; Zhi-yong Ruan (BMC, 2020)
Abstract Background Osteoarthritis (OA) is characterized by inflammation and extracellular matrix (ECM) degradation and is one of the most common chronic degenerative joint diseases that causes pain and disability in adults. Urolithin A (UA) has been widely reported for its anti-inflammatory properties in several chronic diseases. However, the effects of UA on OA remain unclear. The aim of the current study was to investigate the anti-inflammatory effects and mechanism of UA in interleukin-1β (IL-1β)-induced chondrocytes. Results No marked UA cytotoxicity was noted, and UA protected cartilage from damage following IL-1β stimulation in micromasses. Moreover, UA promoted the expression of anabolic factors including Sox-9, Collagen II, and Aggrecan while inhibiting the expression of catabolic factors such as matrix metalloproteinases (MMPs) and a disintegrin and metalloproteinase with thrombospondin motifs 4 (ADAMTS-4) in rat chondrocytes. Protective effects of UA were also observed in ex vivo organ culture of articular cartilage. Mechanistically, IL-1β significantly activated and upregulated the expression of p-ERK 1/2, p-JNK, p-P38, and p-P65, while UA protected chondrocytes against IL-1β-induced injury by activating the mitogen-activated kinase (MAPK)/nuclear factor-κB (NF-κB) signaling pathways. Conclusion Our results provide the evidence that UA could attenuate IL-1β-induced cell injury in chondrocytes via its anti-inflammatory action. UA may be a promising therapeutic agent in the treatment of OA.